Awareness and acceptance of anticipated pediatric COVID-19 vaccination in rural South India - Janardhan, Alok M.; Alok, Sandhya V.; Janardhan, Leelavathi (International Journal of Research in Medical Sciences, 2021)
Background: The objective of this study was to assess the awareness and acceptance of anticipated COVID-19 pediatric vaccination among parents in rural south India. Methods: Objective questionnaire based online cross-sectional study in out-patient department, school WhatsApp groups and the community between 01 July 2021 to 15 July 2021. Sample size 873. Parents of children less than 18 years of age willing to participate in the study were included. Parents not willing to participate in the study were excluded. Results: 64.6% parents accepted pediatric COVID-19 vaccination; 96.4% felt it beneficial to vaccinate children prior to re-opening of school. 96.68% were positive that vaccination in children shall play a pivotal role in the projected third wave. 35.39% were hesitant and wanted to delay vaccinating their children and 14.14% do not believe in vaccine efficacy. 14.53% parents were weary of giving vaccine to their children due to personal experience of adverse effects they had suffered, and 22.45% parents refused vaccination due to hearsay adverse effects. 17.6% parents felt that post COVID-19 infection, children don’t need vaccination. 38.95% of parents were concerned about interaction of COVID-19 vaccine with other vaccines of immunisation schedule, 19.36% felt that children don’t need specific COVID-19 vaccine since the regular immunisation schedule prevents COVID-19 infection. Conclusions: Parents of rural India are aware of the pandemic and its lasting impact in our society but its effect on children is still beyond their comprehension. Most parents are willing and accept pediatric COVID-19 vaccination, however vaccine hesitancy and misconceptions are significant entities that can derail full coverage of children.